2016
DOI: 10.1111/clr.12764
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prospective cohort study on dental implants: clinical and microbiological parameters

Abstract: About 69.4% of implants (75/108) and 67.3% of the patients (35/52) were considered as success in the present prospective cohort study after a mean follow-up of 10.8 years. Microbial follow-up may help to identify patients at risk for peri-implant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
2
31
0
4
Order By: Relevance
“…Finally, based on full‐text assessment, 34 studies were excluded (Table ) yielding eight studies (Daubert et al., ; Donati, Ekestubbe, Lindhe, & Wennström, ; Roccuzzo, Bonino, Dalmasso, & Aglietta, ; Roccuzzo, Gaudioso, Bunino, & Dalmasso, ; Roccuzzo, Savoini, Dalmasso, & Ramieri, ; Simion, Ferrantino, Idotta, & Zarone, ; Tenenbaum et al., ; Zuffetti et al., ) for qualitative synthesis. Out of the final eight publications, four evaluated the prevalence of peri‐implant diseases around implants placed in pristine sites (Donati et al., ; Roccuzzo, Bonino, et al., ; Tenenbaum et al., ; Zuffetti et al., ) (Table a), three in augmented sites (Roccuzzo, Gaudioso, et al., ; Roccuzzo et al. ; Simion et al., ) (Table b) and one in both pristine and augmented sites (Daubert et al., ), respectively (Table c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, based on full‐text assessment, 34 studies were excluded (Table ) yielding eight studies (Daubert et al., ; Donati, Ekestubbe, Lindhe, & Wennström, ; Roccuzzo, Bonino, Dalmasso, & Aglietta, ; Roccuzzo, Gaudioso, Bunino, & Dalmasso, ; Roccuzzo, Savoini, Dalmasso, & Ramieri, ; Simion, Ferrantino, Idotta, & Zarone, ; Tenenbaum et al., ; Zuffetti et al., ) for qualitative synthesis. Out of the final eight publications, four evaluated the prevalence of peri‐implant diseases around implants placed in pristine sites (Donati et al., ; Roccuzzo, Bonino, et al., ; Tenenbaum et al., ; Zuffetti et al., ) (Table a), three in augmented sites (Roccuzzo, Gaudioso, et al., ; Roccuzzo et al. ; Simion et al., ) (Table b) and one in both pristine and augmented sites (Daubert et al., ), respectively (Table c).…”
Section: Resultsmentioning
confidence: 99%
“…Six publications provided data for estimating prevalence of peri‐implant mucositis at patient level (Roccuzzo, Bonino, et al., ; Roccuzzo, Gaudioso, et al., ; Roccuzzo et al. ; Simion et al., ; Tenenbaum et al., ; Zuffetti et al., ). In those publications, data were reported according to subgrouping, resulting in seven clusters for patients with pristine and three clusters for patients with augmented sites, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…; Tenenbaum et al. ). Peri‐implantitis and chronic periodontitis share several biological and clinical characteristics (Berglundh et al.…”
mentioning
confidence: 99%
“…Peri-implantitis, a biological complication, is an inflammatory lesion caused by oral bacteria leading to loss of bone at osseointegrated dental implants (Lang & Berglundh 2011). According to a recent metaanalysis, the overall prevalence of periimplantitis approximates 22% (Derks & Tomasi 2015), confirmed by the first population-based epidemiologic study on periimplantitis (Derks et al 2016;Tenenbaum et al 2016). Peri-implantitis and chronic periodontitis share several biological and clinical characteristics .…”
mentioning
confidence: 99%
“…Since preliminary studies of the osseointegration process, dental implants have been widely used for the rehabilitation of partially or completely edentulous patients over time with high survival rates (Kwon et al 2014;Wang et al 2015;Tenenbaum et al 2016), and represent one of the most important therapeutic advances in modern dentistry (Wilson et al 2016). Despite the high success and survival rates reported for a large number of clinical studies, implant failure has been frequently reported (Laine et al 2005;Yamane et al 2013;Belibasakis et al 2015).…”
mentioning
confidence: 99%